2013
DOI: 10.3747/co.20.1596
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors Associated with the Response to Sunitinib in Patients with Metastatic Renal Cell Carcinoma

Abstract: therapy and confirmed that the mskcc model still appears to be valid for predicting survival in metastatic rcc in the era of molecular targeted therapy. KEY WORDSMetastatic renal cell carcinoma, prognostic factors, sarcomatoid features, first-line therapy, vascular endothelial growth factor, vegf antagonist

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…However, during its construction, several baseline factors potentially influencing the prognosis, including inflammatory markers as C-reactive protein [ 23 ], NLR [ 7 - 13 ], or PLR [ 12 , 14 ], were omitted. Besides, high neutrophils and platelets present in the IMDC model were not independently associated with poor survival in other studies [ 24 , 25 ], and high lymphocyte count was found to decrease risk death of patients treated with interleukin 2 [ 26 ]. Thus, the combination of these may provide more prognostic information than either component alone.…”
Section: Discussionmentioning
confidence: 93%
“…However, during its construction, several baseline factors potentially influencing the prognosis, including inflammatory markers as C-reactive protein [ 23 ], NLR [ 7 - 13 ], or PLR [ 12 , 14 ], were omitted. Besides, high neutrophils and platelets present in the IMDC model were not independently associated with poor survival in other studies [ 24 , 25 ], and high lymphocyte count was found to decrease risk death of patients treated with interleukin 2 [ 26 ]. Thus, the combination of these may provide more prognostic information than either component alone.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies suggested that HB was not only a useful marker for tumor aggressiveness, but also a prognostic factor for distant metastasis [19] . Furthermore, Kawai et al revealed that HB was a factor of specifically promoting bone metastasis from prostate cancer [20] .…”
Section: Discussionmentioning
confidence: 99%
“…The IMDC and MSKCC prognostic scores were calculated at start of second-line therapy, as well as the different factors that form the basis for these established scores (interval between diagnosis and systemic treatment, performance status, hemoglobin levels, corrected serum calcium levels, serum LDH levels, neutrophil and platelet count), presence of sarcomatoid dedifferentiation in 25% of the tumor volume [12], PFS [13] and best response on first-line therapy, the presence of bone metastases [14], brain metastases [15] or glandular metastases (defined as pancreatic, adrenal or thyroid metastases) [16], baseline C-reactive protein (CRP) levels ( or4inferior limit of normal, 5 mg/dl) [17] and albumin levels ( or4inferior limit of normal, 3.5 g/dl) [18,19] at start of second-line therapy. Associations between PFS or OS and potential prognostic factors were assessed using Kaplan-Meier estimates and the logrank test in univariate analysis.…”
Section: Methodsmentioning
confidence: 99%